Growth rate effect on colony formation in directional solidification of Al2O3/YAG/ZrO2. Issue 5 (1st November 2018) - Stelian, Carmen; Cherif, Maya; Carroz, Laurent; Barhalay, Nicolas; Duffar, Thierry
Abstract: Mechanical properties of Al2 O3 /Y3 Al5 O12 /ZrO2 ternary eutectic ceramics are strongly affected by structural defects as pores or colonies. Experimental investigation of the microstructure of this ternary composite indicates that the colonies are generally observed when the solidification occurs at high rates. In this work, the influence of the growth rate on the solid‐liquid interface shape and formation of colonies in directional solidification of Al2 O3 /Y3 Al5 O12 /ZrO2 by Bridgman, Edge‐defined Film‐fed Growth (EFG), and Czochralski (Cz) methods is numerically and experimentally investigated. Numerical modeling of the Bridgman growth process shows large curvatures of the solid‐liquid interface when the pulling rate is increased up to 80 mm/h. The ingots solidified at rates between 5 and 80 mm/h exhibit colony type microstructure. The analysis of EFG growth of ceramic ribbons reveals less curved solid‐liquid interfaces in this system. Numerical modeling shows significant increase in the interface curvature with increasing pulling rate. The microstructure of ribbons grown at pulling rates between 6 and 12 mm/h exhibits colonies only for the ingots solidified at higher rate. Simulations carried out for Czochralski growth process show that the solidification front is almost plane in this system. These results are in agreement with experimental observations showing good structural quality of Cz grown crystals with a flat solid‐liquid interface. Finally it is concluded that formation of colonies in directional solidification of this ternary eutectic composite is linked to large curvatures of the growth interface. Abstract : Numerical and experimental analysis of directionally solidified Al2 O3 /Y3 Al5 O12 /ZrO2 eutectic ceramic by Bridgman method shows that colonies formation is linked to large curvatures of the growth interface.